Judicial control in the European Union reforming jurisdiction in the intergovernmental pillars - Hinarejos Parga, Alicia, 1979- (Oxford : Oxford University Press, 2010)
This text maps out the evolution of judicial control in two major fields of EU activity traditionally outside the scope of its central legal system: the Common Foreign and Security Policy and Justice and Home Affairs.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Jurisdiction -- European Union countries; European Union; Judicial power -- European Union countries; Constitutional courts -- European Union countries; Political questions and judicial power -- European Union countries